LA EXPOSICIÓN A RIESGOS LABORALES DEL PERSONAL DE AGENTES CIVILES DE TRÁNSITO DEL CANTÓN LOJA Y EL ROL DEL TRABAJO SOCIAL - Bermeo Cuaran, Jonathan Alejandro (2018)
The present investigation has like general focus, to determine "THE EXPOSURE TO LABOR RISKS OF THE PERSONNEL OF CIVILIAN TRAFFIC AGENTS OF THE CANTON LOJA AND THE ROLE OF THE SOCIAL WORK", for which they have been raised like specific objectives: 1. To identify the occupational risks and the social impact, as variables of influence in the activities of the personnel of Traffic, 2. Determine the labor risks of the Agents of the Unit based on their social reality, through the RapidMiner software and 3. Build a Manual of Functions as a proposal of prevention of the risks to which the Transit Agents are exposed. The application of a methodology that considers scientific research, which is put at the service of the human being, in his permanent desire to solve problems with bibliographic-documentary support has been made. The conceptual basis will be structured through the active reading of the bibliography, where the analytical - synthetic method will necessarily be very useful, opening the possibility of making deductions of general cases and vice versa. At the same time direct and documentary observation is applied, the first one will allow to locate the study in a more real and specific plane, the second will make possible the information of the Institution under study; as well as the review of other similar investigations. The survey technique has been used as a tool for data collection, which has been directed to the staff of the Operational Traffic Control Unit and road users to organize, tabulate and present the information obtained and thus analyze the results. 5 In addition, the following tools will be used, observation to gather information through maps or sketches, field diaries, observation guides, survey and the SWOT that has allowed to know the strengths, opportunities, weaknesses and threats that exist in the Operational Control Unit of Transit. Through this process, truthful results have been obtained in the analysis of the problem that incurs against the Safety and Labor Welfare of the Traffic Operative Control Unit personnel, thus identifying the eminent risks to which the personnel are exposed, against the social impact in the fulfillment of its functions. The AFFECTATIONS are linked in terms of social control, corresponding to the ordering of traffic and the control of sustainable mobility as impact activities by traffic personnel, functions that by their nature are exposed to contamination (auditory and vehicular) , climatic changes, psychological affectations in the future (stress, bad mood, bad attention of the road user) that affect your health with different types of diseases derived from the fulfillment of your tasks (chronic respiratory diseases, digestive diseases, skin affectations, auditory and visual).